The role of resources and capabilities in managing and overcoming the financial crisis: a case study of the Fratelli Pinna sheep-dairy business. (4th December 2019) - Usai, Antonio; Porcheddu, Daniele; Arru, Brunella
The Italian economic system comprises a significant number of small and medium-sized family businesses. Recent empirical evidence shows that the characteristics of family firms are crucial in overcoming the adverse effects of the financial crisis, thus contributing to the generation of wealth and employment for the country. Using the case study approach, this paper investigates the firm-level dynamics during the last economic recession of a medium-size family firm, operating in a mature market and situated in a rural context. The finding showed that the management approach to the crisis was dictated, among various factors, by the firms distinctive characteristics, its social capital and its role in the local and regional contexts. These peculiarities have been the key to overcoming the most harmful effects of the economic crisis and to avoiding the necessity of carrying out radical restructuring processes and financial recovery. Moreover, this case showed the pivotal role of the social dimension of the firm and the consequences of the decrease in the historical attention placed on the well-being of the business community and society as a whole.